Health wearables in adolescents: implications for body satisfaction, motivation and physical activity. Issue 4 (4th July 2019) - Kerner, Charlotte; Burrows, Adam; McGrane, Bronagh
ABSTRACT: Significant proportions of adolescents do not meet recommended physical activity levels. Finding new ways to motivate adolescents to be active is important for physical and psychological well-being. Health and fitness wearables such as the Fitbit have the potential to motivate young people to be active. The aim of this study is to explore if wearing a Fitbit for 5 weeks impacted adolescents' (14–15 year olds) body satisfaction, physical activity motivation and objective physical activity. The study was conducted with 62 (38 boys, 24 girls) pupils aged 14–15, from five high school physical education classes, in one high school in the United Kingdom. Pupils wore a Fitbit Charge HR for 5 weeks. Pupils wore an accelerometer for 7 days pre and post the 5-week period to explore changes in physical activity levels. Pupils also completed pre-post-test questionnaires to measure body satisfaction and physical activity motivation. Data were analysed using a repeated measures Multivariate Analysis of Variance to explore differences in scores between time and sex. After wearing the Fitbit, the pupils experienced declines in autonomous motivation and increases in both amotivation and controlled motivation, but these differences were not significant. In line with these negative motivational outcomes, pupils engaged in significantly less moderate to vigorous physical activity after wearing the Fitbit. Significant increases in body satisfaction were also experienced by pupils after wearing the Fitbit. These findings suggest that without support Fitbits may make pupils less motivated to be active and decrease the physical activity levels of adolescents.